PENDISTRIBUSIAN ZAKAT MAL PADA MASYARAKAT DI KELURAHAN MAYANG MANGURAI KECAMATAN ALAM BARAJO KOTA JAMBI - Haslinda; Dedek Kusnadi (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
This study aims to analyze Distribution of Zakat Mal in the Mayang Mangurai Community, Alam Barajo District, Jambi City. Zakat has a strategic role in overcoming poverty and creating socio-economic balance. This study uses a descriptive qualitative approach with data collection methods through observation, in-depth interviews, and documentation. The results of the study indicate that the diverse economic conditions of the community, ranging from fixed income to informal work, affect the classification of zakat recipients (mustahik). In addition, social factors such as awareness of zakat, mutual cooperation values, and geographical proximity to the mosque also determine the distribution of zakat. Other findings show that the distribution of zakat tends to prioritize residents around the mosque, which has the potential to cause inequality in receipt. Therefore, a more inclusive and needs-based zakat distribution system is needed to ensure social justice and the effectiveness of zakat as an instrument for empowering the community.